(untitled) (Perner’s Contacts, 2012)
New trends how to replace at least part of the road transport, and if possible transfer it to rail or water transport were initially met with incomprehension or inability to technologically and financially provision to ensure the development and testing of the system. This paper describes a new system for road-to-rail vehicles (semi-trailers and semi-trailers for vertical transhipment) for railways. This is a description of new technologies in the transhipment of these vehicles on rail waggons and their consecutive transportation by rail.